2021
DOI: 10.1016/j.nephro.2020.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Le rôle du registre national REIN en France dans la veille sanitaire des patients en insuffisance rénale chronique terminale infectés par le SARS-CoV-2 : organisation et premières données

Abstract: Since January 2020 Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre -including this research content -immediately available in PubMed Central and other publicly funded repositories, such as the WHO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Our study confirms the impact observed on the prevalence of COVID-19 in kidney transplant recipients (KTR) or chronic hemodialysis patients (34.6% vs 7.8%) [12]. The frequency of SARS-CoV-2 infection was approximately 1.8% of KTR patients and 4.9% of dialysis patients in the REIN cohort [13], while this incidence was 1.9% in the study of Ismail [14].Some studies have shown that most KTR with COVID-19 worldwide are men with an average age of over 50 years [15,16]. The average age of our patients was 34.1 ± 11.6 years (31.8% were aged≥ 50 years), of which 29 patients (69.5%) were men.…”
Section: Discussionsupporting
confidence: 86%
“…Our study confirms the impact observed on the prevalence of COVID-19 in kidney transplant recipients (KTR) or chronic hemodialysis patients (34.6% vs 7.8%) [12]. The frequency of SARS-CoV-2 infection was approximately 1.8% of KTR patients and 4.9% of dialysis patients in the REIN cohort [13], while this incidence was 1.9% in the study of Ismail [14].Some studies have shown that most KTR with COVID-19 worldwide are men with an average age of over 50 years [15,16]. The average age of our patients was 34.1 ± 11.6 years (31.8% were aged≥ 50 years), of which 29 patients (69.5%) were men.…”
Section: Discussionsupporting
confidence: 86%
“…With the help of the REIN clinical research assistants, the nephrologists reported infection by SARS-CoV-2 in the registry in the presence of suspicious clinical symptoms, characteristic signs on CT chest scan or a positive RT-PCR result for SARS-CoV-2 on a nasopharyngeal swab. A form reporting their initial condition and outcome was filled in for each patient [ 9 , 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the REIN registry, backed by its expertise and national network, was able to set up epidemiological monitoring of chronic dialysis and/or transplant patients affected by SARS-CoV-2 very quickly ( 95 ). A weekly newsletter has been set up (still on-going), sent to all nephrologists, using information transmitted by all the REIN research assistant working with the nephrologists in the regions.…”
Section: Prospects For Renal Registries and Researchmentioning
confidence: 99%